Drivers and indicators of the EU rural development expenditure mix across space: Do neighbourhoods matter?. (November 2019) - Camaioni, B.; Coderoni, S.; Esposti, R.; Pagliacci, F.
Highlights: We analyse the 2007–2013 Rural Development Programmes' expenditure for EU-27. The dataset comprises 1288 NUTS-3 regions' expenditure for 43 RDP measures. We use local indicators and drivers of expenditure mix, plus neighbours' features. Spatial dependence in spending patterns emerges, particularly for agro-environment. Ex-post expenditure valuation should properly consider spatial scale and dependence. Abstract: This paper analyses the 2007–2013 Rural Development Programmes' expenditure mix within the EU-27 space. Its major novelty consists in using indicators and methods combining a high level of expenditure disaggregation across both regions and measures to assess the drivers of the expenditure mix at a more local level. At the adopted scale of analysis, the rurality degree of any region, the rurality of the neighbours and their respective expenditure patterns are explicitly considered. Results suggest that more rural regions spend more funds as expected, but their expenditure mix, and the share of agro-environmental payments in particular, also depends on the characteristics of the neighbouring space, thus confirming the presence of spatial dependence in spending patterns and the need of its explicit consideration in any ex-post expenditure assessment.